2006
DOI: 10.1038/sj.onc.1209890
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α contributes to tumour-selective killing by the sigma receptor antagonist rimcazole

Abstract: We have previously reported tumour-selective killing by the sigma (r) receptor ligand rimcazole. We now report that rimcazole elevates hypoxia inducible factor-1a (HIF-1a) protein levels under normoxic conditions in colorectal (HCT-116) and mammary carcinoma (MDA MB 231) cells but fails to induce HIF-1a in normal fibroblasts or mammary epithelial cells. Combining the r-1 agonist ( þ )-pentazocine with rimcazole substantially reduces the accumulation of HIF-1a, confirming that the effect is mediated at least pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Interestingly, sigma-1 receptors have also been linked to HIF1a. The blockade of sigma-1 receptors by the putative antagonist rimcazole in normoxic colorectal and mammary carcinoma cells increases HIF1a, but with a cytotoxic effect in this case (Achison et al, 2007). Thus, regulation of HIF1a by sigma-1 and sigma-2 receptor subtypes may be complex, with different viability outcomes depending on cell type and sigma ligand.…”
Section: Activation Of Sigma-2 Receptor Induces Metabolic Stimulationmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, sigma-1 receptors have also been linked to HIF1a. The blockade of sigma-1 receptors by the putative antagonist rimcazole in normoxic colorectal and mammary carcinoma cells increases HIF1a, but with a cytotoxic effect in this case (Achison et al, 2007). Thus, regulation of HIF1a by sigma-1 and sigma-2 receptor subtypes may be complex, with different viability outcomes depending on cell type and sigma ligand.…”
Section: Activation Of Sigma-2 Receptor Induces Metabolic Stimulationmentioning
confidence: 90%
“…A hallmark of cells undergoing glycolysis under normoxic conditions (aerobic glycolysis) is the expression of HIF1a. A link between treatment of tumor cells with the sigma modulator rimcazole and increased expression of HIF1a has been established previously (Achison et al, 2007). Therefore, we decided to investigate whether this transiently expressed protein might be stabilized or increasingly translated upon treatment with CM764.…”
Section: Cm764-induced Production Of Rosmentioning
confidence: 93%
“…Mutations in the TP53 gene, which are strong determinants of chemoresistance, do not affect the sensitivity of cancer cells to sigma-2-induced apoptosis [63,[79][80][81]. Moreover, sigma-2 induced apoptosis can be caspase-independent [80,81] and may therefore also occur in cells with caspase dysfunction.…”
Section: Mechanisms Underlying Cytotoxicitymentioning
confidence: 99%
“…Previous reports have suggested that following insult, sigma 1 receptor agonists promote cell survival, while sigma 1 receptor antagonism tends to promote cell death (Achison et al, 2007; Antonini et al, 2009; Maurice and Su, 2009; Ruscher et al, 2011; Spruce et al, 2004; Tchedre and Yorio 2008; Yang et al, 2007). The present study, which uses a novel set of D2-like dopamine and sigma receptor selective compounds, suggests that under certain conditions sigma 1 antagonists may also act as potent neuroprotectants.…”
Section: Discussionmentioning
confidence: 99%